Diagnostic and Interactive Use of PMM by Japanese Local Governments: Does the Context Affect the Fitness of Use?. Issue 1 (2nd January 2021) - Yetano, Ana; Matsuo, Takami; Oura, Keisuke
Abstract: Efforts to "reinvent" government have emphasized the importance of performance measurement and management (PMM) systems to improve government operations. Although it seems clear why organizations adopt PMM systems, less is known about their actual consequences. This study, using a survey to Japanese local government departments, explores whether different uses of PMM and their interaction with the context (predictability and bureaucratic culture) can affect the impact of PMM on organizational performance. Results show that using PMM, not only having it, is not enough to generate performance improvements. It is shown that the fitness of use to the local government context is the way to foster performance. A strong bureaucratic culture shows a positive relation with performance in the Japanese setting.